Advances in light-emitting metal-halide perovskite nanocrystals. (June 2020) - Xu, Liang-Jin; Worku, Michael; He, Qingquan; Ma, Biwu
Abstract: Abstract : Metal-halide perovskites, in particular their nanocrystal forms, have emerged as a new generation of light-emitting materials with exceptional optical properties, including narrow emissions covering the whole visible region with high photoluminescence quantum efficiencies of up to near-unity. Remarkable progress has been achieved over the last few years in the areas of materials development and device integration. A variety of synthetic approaches have been established to precisely control the compositions and microstructures of metal-halide perovskite nanocrystals (NCs) with tunable bandgaps and emission colors. The use of metal-halide perovskite NCs as active materials for optoelectronic devices has been extensively explored. Here, we provide a brief overview of recent advances in the development and application of metal-halide perovskite NCs. From color tuning via ion exchange and manipulation of quantum size effects, to stability enhancement via surface passivation, new chemistry for materials development is discussed. In addition, processes in optoelectronic devices based on metal-halide perovskite NCs, in particular, light-emitting diodes and radiation detectors, will be introduced. Opportunities for future research in metal-halide perovskite NCs are provided as well.